Mucosal prolapse polyp masquerading as malignancy: A rare case report (Indian Journal of Case Reports, 2019)
Mucosal prolapse polyp is a variant of mucosal prolapse syndrome which comprises of various clinical and histopathological entities, with mucosal prolapse as the underlying pathogenic mechanism. We present the case of a 17-year-old male with a history of mucous discharge per rectum. Colonoscopy revealed ulceroproliferative polypoid growth in distal rectum at 18cm from the anal verge. Polypectomy was done which showed polypoid rectal mucosa with branching and distortion of crypts. Splaying of muscle fibers into lamina propria, mixed inflammatory cell infiltrate and fibrosis was noted. After review of clinical history and histopathology, the patient was diagnosed to have mucosal prolapse polyp, a variant of mucosal prolapse syndrome. Here, we present this rare case to enlighten the importance of identifying mucosal prolapse syndrome as the treatment plan completely changes.